2020
DOI: 10.30880/jtmb.2020.07.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Power Distance and Uncertainty Avoidance on Employees’ Job Performance: Preliminary Findings

Abstract: This study examines the relationship between corporate culture and employees' job performance in a multinational company operated in Malaysia. Malaysia is well-known as a culturally-diverse country in the world. Therefore, the selected multinational company needs to assessits internal cultures as workers from different ethnical backgrounds work together. Thegeneralobjectiveof this studyis to determine corporate culture's effect on job performance among the workers in the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Accordingly, Hypotheses H1a-H5a and H1b-H5b that postulate the effects of national culture on job performance proposed in this study are all supported. This research finding is consistent with the previous studies of Jung et al (2008), Taras et al (2011), Lu and Lin (2014), Vitolla et al (2019), andJie et al (2020). The results also found that transformational leadership had a positive influence on employee job performance; these findings are in line with those reported in the studies of Gardner and Avolio (1998), Jung and Avolio (1999), Buil et al (2019), and.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, Hypotheses H1a-H5a and H1b-H5b that postulate the effects of national culture on job performance proposed in this study are all supported. This research finding is consistent with the previous studies of Jung et al (2008), Taras et al (2011), Lu and Lin (2014), Vitolla et al (2019), andJie et al (2020). The results also found that transformational leadership had a positive influence on employee job performance; these findings are in line with those reported in the studies of Gardner and Avolio (1998), Jung and Avolio (1999), Buil et al (2019), and.…”
Section: Discussionsupporting
confidence: 92%
“…Miao et al (2018) addressed that a leader locates in high uncertainty avoidance cultures will be more likely to communicate operations, procedures, and regulations with their employees, thus resulting in higher task performance. Prior studies demonstrated that the higher the degree of uncertainty avoidance within an organization, the higher the employees' motivation, and lead the high employees' job performance (Miao et al, 2018;Jie et al, 2020). Research on container shipping have addressed that people characterized by high uncertainty avoidance tend to avoid ambiguous situations and are more conscious of rules and procedures (Lu et al, 2012;Lu and Lin, 2014).…”
Section: The Impact Of Cultural Differences On Job Performancementioning
confidence: 99%
“…The predictive effect of organisational culture on job performance have been widely researched in various context and industries such as telecom sector in Pakistan (Fareed et al, 2016), South Korean sports industry (Jeong et al, 2019), consulting companies in Indonesia (Raharjo et al, 2018), among SMEs in Pakistan (Soomro & Shah, 2019) and steel industry in Taiwan (Kuo & Tsai, 2019). In Malaysia, similar results were found among multinational company in Sarawak (Lau et al, 2020) and SME employees' in Johor, Penang, Selangor and Perak (Krishnan et al, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…In an environment with low power distance, members of the society strive to balance power circulation and seek justification for the unequal distribution of power (Hofstede, 2011 cited from Hofstede, 1980). According to Jie et al. (2020) power distance has a considerable and relatively favorable effect on employees' job performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In an environment with low power distance, members of the society strive to balance power circulation and seek justification for the unequal distribution of power (Hofstede, 2011cited from Hofstede, 1980. According to Jie et al (2020) power distance has a considerable and relatively favorable effect on employees' job performance. The study emphasized that the chosen international firm should look for ways to improve and reinforce the power distance dimension, as they impact workers' job performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%